Physical training of students with the round-concave and round back and different levels of biogeometric profile of posture - Vypasniak, Igor; Shankovsky, Andriy (Journal of Education, Health and Sport, 2017)
Topicality. At the present stage of the development of the society, the state of health of student youth is one of the most important indicators of a nation’s healthy potential. Therefore, its preservation and strengthening is of paramount importance. Today, against the background of the growing decrease of motor activity, there is an aggravation of the problem of the proliferation of functional disorders of the musculoskeletal system among the student youth. Research Objectives: to study the physical preparedness of students with round-concave and rounded back and different levels of biogeometric profile. Research Results. The negative tendency of the deterioration of the posture of the students of the 1-4 courses has been established. It was determined that in the first year of study 11.3% of students with functional impairment of posture have a round spine, in the second year – 13.9%, in the third year – already 16.5%. The comparative characteristic of physical preparedness of students with different types of functional posture disorders has shown that among the students with a round spine, regardless of their biogeometric posture profile, there is also a general negative tendency of deteriorating the manifestation of endurance of the muscles of the trunk, upper limbs and back, and the flexibility of the vertebral column, mobility of hip joints and elasticity of popliteal tendons. Characteristics of physical preparedness of students with round-concave backs testifies the presence of differences in the level of manifestation of individual qualities. The 4th year students with a low level of the posture biogeometric profile had lower average values for the strength of the muscles of the body and strength of the muscles of the upper extremities and back compared with the students of the first year of study. Conclusions. The determining of the morphofunctional characteristics of students with different types of posture is the basis for the development of the concept of the prevention and correction of functional disorders of the musculoskeletal system of students in the process of physical education.